Inter-Individual Variability in Fear of Humans and Relative Brain Size of the Species Are Related to Contemporary Urban Invasion in Birds - Carrete, Martina (Public Library of Science, 2011)
BACKGROUND: Urbanization is the most prevailing cause of habitat transformation worldwide, differing from others by its intense levels of human activity. Despite its obvious impact on wildlife, it is still unclear why and how some species are able to adapt to urban settings. One possibility is that fear of humans and vehicles could preclude most species from invading cities. Species entering urban environments might be those that are more tolerant of human disturbance (i.e., tame species). Alternatively or in addition, urban invaders could be a fraction of variable species, with “tame” individuals invading urban habitats and other individuals remaining in rural areas. METHODOLOGY: Using the contemporary urban invasion by birds in a recently established South American city, we tested both hypotheses by relating interspecific differences in invasiveness to their flight initiation distances (i.e., the distances at which birds flee from approaching cars, FID), as well as to their relative brain size (RBS), a correlate of measures of behavioral flexibility. PRINCIPAL FINDINGS: Urban invasiveness was not significantly related to species' average rural FIDs but positively related to their RBS and inter-individual variability in FID. Moreover, FIDs were consistently lower in urban than in rural conspecifics, and the FIDs of urban individuals were within the lower-range distribution of their rural conspecifics. RBS indirectly influenced urban invasion through its positive effect on inter-individual variability in FID. CONCLUSIONS/SIGNIFICANCE: Urban invaders do not appear to be individuals from apparently tame species, but rather tame individuals from species with a variable response regarding fear of people. Given the positive relationship between RBS and inter-individual variability in FID, our results suggest that behavioural flexibility should be regarded as a specific trait encompassing variability among individuals. Further research is needed to ascertain the neurophysiological mechanisms underlying the relationship between brain size and inter-individual variability in behavioural traits.